Large Vessel Occlusion in Patients With Minor Ischemic Stroke in a Population-Based Study. The Dijon Stroke Registry - Duloquin, Gauthier; Crespy, Valentin; Jakubina, Pauline; Giroud, Maurice; Vergely, Catherine; Béjot, Yannick (Frontiers in Neurology, 2022)
Introduction: Strategy for the acute management of minor ischemic stroke (IS) with large vessel occlusion (LVO) is under debate, especially the benefits of mechanical thrombectomy. The frequency of minor IS with LVO among overall patients is not well established. This study aimed to assess the proportion of minor IS and to depict characteristics of patients according to the presence of LVO in a comprehensive population-based setting. Methods: Patients with acute IS were prospectively identified among residents of Dijon, France, using a population-based registry (2013–2017). All arterial imaging exams were reviewed to assess arterial occlusion. Minor stroke was defined as that with a National Institutes of Health Stroke Scale (NIHSS) score of <6. Proportion of patients with LVO was estimated in the minor IS population. The clinical presentation of patients was compared according to the presence of an LVO. Results: Nine hundred seventy-one patients were registered, including 582 (59.9%) patients with a minor IS. Of these patients, 23 (4.0%) had a LVO. Patients with minor IS and LVO had more severe presentation [median 3 (IQR 2–5) vs. 2 (IQR 1–3), p = 0.001] with decreased consciousness (13.0 vs. 1.6%, p<0.001) and cortical signs (56.5 vs. 30.8%, p = 0.009), especially aphasia (34.8 vs. 15.4%, p = 0.013) and altered item level of consciousness (LOC) questions (26.1 vs. 11.6%, p = 0.037). In multivariable analyses, only NIHSS score (OR = 1.45 per point; 95% CI: 1.11–1.91, p = 0.007) was associated with proximal LVO in patients with minor IS. Conclusion: Large vessel occlusion (LVO) in minor stroke is non-exceptional, and our findings highlight the need for emergency arterial imaging in any patients suspected of acute stroke, including those with minor symptoms because of the absence of obvious predictors of proximal LVO.